2018
DOI: 10.1108/ccij-04-2017-0034
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting high-reliability organizing: obstacles to safety and resilience

Abstract: Purpose The purpose of this paper is to complicate and critique contemporary scholarship on high-reliability organizations (HROs). This paper argues that although HRO scholarship helps to identify communicative patterns that facilitate reliability and safety, it also simplifies processes that undermine the effectiveness of existing recommendations for HROs. Design/methodology/approach This paper frames high-reliability organizing as the enactment of mindfulness, which is the theoretical mechanism behind each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
1
13
0
1
Order By: Relevance
“…Where Weick and Sutcliffe (2001) focused almost exclusively on the internal behavioural aspects of organizational actors directly or indirectly involved with managing unexpected events, Casler's model appeared to posit an aspect of accountability by acknowledging the presence of societal performance demands. Other literature in our study (e.g., Bourrier, 2011; Ford, 2018; Gebauer, 2013; Vogus, 2012) also suggested an awareness or mindfulness of factors eternal to the organization and alluded to the need to respond to them in some way. van Stralen (2015) suggested that the manner an organization responds to ambiguity may reflect its level of HRO‐like behaviour.…”
Section: Results/findingssupporting
confidence: 75%
“…Where Weick and Sutcliffe (2001) focused almost exclusively on the internal behavioural aspects of organizational actors directly or indirectly involved with managing unexpected events, Casler's model appeared to posit an aspect of accountability by acknowledging the presence of societal performance demands. Other literature in our study (e.g., Bourrier, 2011; Ford, 2018; Gebauer, 2013; Vogus, 2012) also suggested an awareness or mindfulness of factors eternal to the organization and alluded to the need to respond to them in some way. van Stralen (2015) suggested that the manner an organization responds to ambiguity may reflect its level of HRO‐like behaviour.…”
Section: Results/findingssupporting
confidence: 75%
“…Some researchers also state that high reliability organizations face minimum errors and risks due to their continuous efforts to promote safety. Employees working in these organizations show positive behaviors (Thomassen et al, 2011 ; Ford, 2018 ). Since safety specific transformational leaders transform employees by encouraging safe behavior at the workplace (Veazie et al, 2019 ), the COVID-19 perceived risk reduces as employees automatically start perceiving that their leader is making extra efforts to ensure their safety which enhances their psychological well-being.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…The proposed model gets its support from the high reliability organizational theory (Roberts, 1990 ; La Porte, 1996 ), which states that organizations can minimize occupational hazards by taking sufficient safety measures. This theory states that high reliability organizations minimize occupational risks by engaging in activities that promote employee safety, which is beneficial for employees (Ford, 2018 ). We believe that transformational leaders and safety-conscious employees decrease COVID-19 perceived risk among employees, enhancing their psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…The turnover intention scale was omitted since it is a one item measure. All the variables were measured with Likert response scales, thus, considering the ordinal nature of the data (Field, 2013) the method of estimation used was ULSMV. Model fit was evaluated by considering the chi-square statistic as well as a few other goodness of fit indices, namely, the root mean square error of approximation (RMSEA; Steiger, 1990), the comparative fit index (CFI; Bentler, 1990), and the Tucker Lewis index (TLI; Tucker & Lewis, 1973).…”
Section: Article In Pressmentioning
confidence: 99%
“…Furthermore, given that participation was voluntary and convenience sampling was used, this may have attracted atypical respondents with special interests in safety which could affect the generalizability of the data. That being said, most behavioural science research relies on self-report measures and these kinds of measures form the basis of much well-known theory (Field, 2013). Some authors argue that people's perception of a given reality is often more powerful than the objective truth about such a reality (Hendriks et al, 2015).…”
Section: Limitations and Directions For Further Researchmentioning
confidence: 99%